2020
DOI: 10.3390/cancers12092533
|View full text |Cite
|
Sign up to set email alerts
|

Potential Role of PDGFRβ-Associated THBS4 in Colorectal Cancer Development

Abstract: Colorectal cancer is a significant cause of death since it frequently metastasizes to several organs such as the lung or liver. Tumor development is affected by various factors, including a tumor microenvironment, which may be an essential factor that leads to tumor growth, proliferation, invasion, and metastasis. In the tumor microenvironment, abnormal changes in various growth factors, enzymes, and cytokines can wield a strong influence on cancer. Thrombospondin-4 (THBS4), which is an extracellular matrix pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…However, several investigators have reported that TSP-4 exerts pro-angiogenic activities in tissue remodeling and tendinopathy development (49,50). Similar pro-angiogenic activities of TSP-4 have been reported through in vivo and in vitro studies on breast cancer and colorectal cancer (51,52).…”
Section: Discussionsupporting
confidence: 59%
“…However, several investigators have reported that TSP-4 exerts pro-angiogenic activities in tissue remodeling and tendinopathy development (49,50). Similar pro-angiogenic activities of TSP-4 have been reported through in vivo and in vitro studies on breast cancer and colorectal cancer (51,52).…”
Section: Discussionsupporting
confidence: 59%
“…Recently, it was found that there are increased levels of THBS4 in colorectal cancer patients and it is highly associated with PDGFRβ expression in tumor tissues compared to normal tissues [20]. Further, the expression level of THBS4 was also significantly increased with increased expression of PDGFRβ, despite no significant changes in mRNA [20].…”
Section: Thrombospondinmentioning
confidence: 99%
“…MMP and LOX promote collagen degradation and cross-linking, respectively [18,19]. Recently, we found increased levels of THBS4, an ECM protein, is highly associated with PDGFRβ expression in tumor tissues when compared to normal tissues of colon cancer patients [20].…”
Section: Introductionmentioning
confidence: 98%
“…As a secreted extracellular matrix protein, THBS4 has been reported mediated angiogenesis responding to TGF-β signaling [37]. THBS4 in favor of an oncogene in colorectal cancer [38], prostate cancer [39], and hepatocellular carcinoma [40]. Compared to normal tissues, THBS4 expression at a higher level in those cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to normal tissues, THBS4 expression at a higher level in those cancers. In colorectal cancer, THBS4 secretion induced by TGFβ/ PDGFRβ pathways and promoted adhesion, migration, and proliferation of colorectal cancer [38]. And THBS4 might as a potential therapeutic target in prostate cancer, inhibited expression of THBS4 could impede the PI3K/Akt signaling and disturb the cancer stem cell (CSC)-like properties [39].…”
Section: Discussionmentioning
confidence: 99%